The genus Rhinoglena (Rotifera, Monogononta, Ephiphanidae) in North America, with the description of two new species - Segers, Hendrik; Walsh, Elizabeth J. (Zootaxa, 2017)
Based on material from aquatic habitats in the northern Chihuahuan Desert and a literature review, we present an account on the occurrence of genus Rhinoglena in North America. Two new species are described, and the presence of Rhinoglena frontalis in the USA is confirmed. Of the two new species, R. texana n. sp. is a close relative of R. frontalis, whereas R. ovigera n. sp. is unique by being oviparous, in contrast to all other Rhinoglena which are viviparous. This prompts a revision of the generic diagnosis of Rhinoglena to accommodate the new species. An identification key to the known species of the genus is provided.